Psb34 protein modulates binding of high-light-inducible proteins to CP47-containing photosystem II assembly intermediates in the cyanobacterium Synechocystis sp. PCC 6803 - Rahimzadeh-Karvansara, Parisa; Pascual-Aznar, Guillem; Bečková, Martina; Komenda, Josef (Photosynthesis research, 2022)
Assembly of photosystem II (PSII), a water-splitting catalyst in chloroplasts and cyanobacteria, requires numerous auxiliary proteins which promote individual steps of this sequential process and transiently associate with one or more assembly intermediate complexes. In this study, we focussed on the role of a PSII-associated protein encoded by the ssl1498 gene in the cyanobacterium Synechocystis sp. PCC 6803. The N-terminal domain of this protein, which is here called Psb34, is very similar to the N-terminus of HliA/B proteins belonging to a family of high-light-inducible proteins (Hlips). Psb34 was identified in both dimeric and monomeric PSII, as well as in a PSII monomer lacking CP43 and containing Psb28. When FLAG-tagged, the protein is co-purified with these three complexes and with the PSII auxiliary proteins Psb27 and Psb28. However, the preparation also contained the oxygen-evolving enhancers PsbO and PsbV and lacked HliA/B proteins even when isolated from high-light-treated cells. The data suggest that Psb34 competes with HliA/B for the same binding site and that it is one of the components involved in the final conversion of late PSII assembly intermediates into functional PSII complexes, possibly keeping them free of Hlips. Unlike HliA/B, Psb34 does bind to the CP47 assembly module before its incorporation into PSII. Analysis of strains lacking Psb34 indicates that Psb34 mediates the optimal equilibrium of HliA/B binding among individual PSII assembly intermediates containing CP47, allowing Hlip-mediated photoprotection at all stages of PSII assembly.
Keywords: Photosynthesis; protein TNFSF14; Bacterial Proteins; Photosystem II Protein Complex; Tumor Necrosis Factor Ligand Superfamily Member 14; High-light-inducible protein; Synechocystis; fotosystém II (proteinový komplex); fotosyntéza; CP47; bakteriální proteiny; Photosystem II